2015
DOI: 10.1016/j.envpol.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of organochlorine pesticides in the environmental matrices from King George Island, west Antarctica

Abstract: a b s t r a c tAntarctica is considered as a final sink of many persistent organic pollutants (POPs). This work aims to investigate the levels, distributions and potential sources of organochlorine pesticides (OCPs) with HRGC/ HRMS technique. Twenty-three OCPs were measured in various environmental matrices from King George Island, west Antarctica. The total concentrations (S 23 OCPs) were at quite low levels, ranging 93.6 e1260 pg g À1 dry weight (dw) in soil and sediment, 223e1053 pg g À1 dw in moss and 373e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The analytical procedure followed our previous methods with some minor modifications (Wang et al, 2015;Zhang et al, 2015). Briefly, the samples were extracted by accelerated solvent extraction (ASE, ASE 300, Dionex, USA).…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
“…The analytical procedure followed our previous methods with some minor modifications (Wang et al, 2015;Zhang et al, 2015). Briefly, the samples were extracted by accelerated solvent extraction (ASE, ASE 300, Dionex, USA).…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
“…However, it has been still in use in some countries especially to control the vectors of malaria [30,31]. Several scientists have also reported the presence of DDT in air, soil, water, sediment, snow, lichen and mosses samples from 5 to ~15000 pg/g or pg/L [16,18,32] including food chains of the biotic components of Antarctic ecosystem [26]. According to UNEP [33], production of 6300t of DDTs was done by India alone in 2003, therefore, it is not surprising to find the traces of DDTs in the Antarctic ecosystem.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have reported the pesticides and polycyclic aromatic hydrocarbons (PAHs) in lake water [2,12], marine atmosphere/air [13][14][15], soil/sediment [16][17][18][19], snow [12], mosses [16,18,20], lichen [16,19,20], krill [21], penguin [22][23][24][25], skua blood [23,24]. A detailed review of the presence of persistent organic pollutants in abiotic and biotic components studied nationally and internationally [26].…”
Section: Contamination Of Lakes In Broknes Peninsula East Antarcticamentioning
confidence: 99%
“…Overall, the average concentrations of 4, 4'-DDT was greater than the concentrations of other metabolites in each of the three zones. The high percentage of total DDT occurring as 4, 4'-DDT in soils might be an indication that the DDT in these soils was just recently deposited [11].Yadavet al [14] also reported higher DDT concentrations in agricultural soils of Nepal; this is because large quantities of DDT are used in agricultural activities than other metabolitesand that it has lower tendencies to biodegrade [15]. Two metabolites 4,4'-DDT and 4,4'-DDE show a decline in concentrations from zone A to C, the same cannot be said of 4,4'-DDD which had its highest mean concentration levels in zone B followed by zone A then very low concentrations in zone C. In zones A and B the mean concentration of 4,4'-DDT was approximately twice that of 4,4'-DDD and 4,4'-DDE but in zone C there was little difference in concentration between the three metabolites.…”
Section: Concentrations Of Ddt and Its Metabolites In Soil Of Tshilamusimentioning
confidence: 99%
“…Butte [20] reported that the exposure could be as a result of ingestion of non-food items and regular hand to mouth contact. In a rural area like Tshilamusi with no pavements, small children spend most of their time outdoors playing and even eating the soil during games hence there is high risk of exposure.Once DDT has been sprayed on the walls of the huts it is now subject to different agents of weather and different physiochemical reactions which will determine the distance and rate of travel from the area of application [14]. In this study, there was a huge difference in the total DDT detected in each of the 3 zones, with Zone A as expected having the highest concentrations followed by B then C. This can be attributed to the obvious fact that more DDT is found in the zone wherein its sprayed yearly and also the other reason is the fact that once it is in the soil it will required processed such as erosion, dispersion and heavy winds to move the DDT into other zones [21].…”
Section: Distribution Of Ddt and Its Metabolites In Tshilamusi Homestmentioning
confidence: 99%